Persepsi Peserta Didik terhadap Pembelajaran Biologi Terintegrasi Nilai-Nilai Islam di Fase F MAN Se-Kota Padang Panjang - Tri Ulfi Mardiyah; Ardi Ardi (Al-Alam: Islamic Science Education Journal, 2026)
This study aims to describe students' perceptions of biology learning integrated with Islamic values ​​in MAN throughout Padang Panjang City. This research is a quantitative descriptive study. The study population was 277 students of grade XI (phase F) MAN throughout Padang Panjang City, with a sample of 136 students determined using simple random sampling techniques through the Slovin formula. Data were obtained through interviews with biology teachers and the distribution of Likert scale questionnaires consisting of 33 statements. Data were analyzed descriptively using percentages, averages (means) with the help of Excel. The results showed that students' perceptions of the integration of Islamic values ​​in biology learning were in the good category, with a percentage of 27.2% in the very good category, 61% in the good category, and 11.8% in the fairly good category. Results based on indicators indicate that the integration of Islamic values ​​has a positive impact on students' attention, mindset, assessment system, and personality type. Therefore, biology learning integrated with Islamic values ​​can be a holistic learning alternative for enhancing both academic understanding and spiritual values ​​in students at madrasahs.